Effect of palm oil fuel ash (POFA) to steel fibre concrete towards drying shrinkage and heat of hydration - Rasyiqah Afif, Md Ishak (2018)
Pozzolan material is material that consist of siliceous or aluminous. Pozzolan in the presence of moisture can react with calcium hydroxide (Ca(OH)2) to form Calcium-Silicate-Hydrate gel (CSH gel) that responsible for the strength in cement based material. Pozzolanic material are produced by combustion of the waste from natural or artificial material. In this study, Palm Oil Fuel Ash (POFA) was utilized as pozzolanic material in concrete. POFA is by product from biomass product of power plant whereby oil palm residue such as fibre, shells and empty fruit bunches are burnt to generate electricity. The size of POFA is 63μm and Portland cement type 1 was partial replace by 10%, 20% and 30% of POFA by weight of cement used in order to observe the behavior of POFA as a cement replacement to steel fibre concrete in reducing temperature during hydration and drying shrinkage due to different percentage of partial cement replacement. The result of heat of hydration tests revealed that POFA as a partial cement replacement towards steel fibre concrete reduces the amount of temperature and delay the time which the peak temperature occurs at 30% of POFA as a cement replacement. Other than that, the drying shrinkage test result showed that the steel fibre concrete containing 30% of POFA as a partial cement replacement was much less shrinkage compared to other sample. This study implies that POFA is a good and beneficial especially in the construction of steel fibre concrete as a cement replacement.